2013
DOI: 10.5935/0103-507x.20130048
|View full text |Cite
|
Sign up to set email alerts
|

Brain death and tissue and organ transplantation: the understanding of medical students

Abstract: ObjectiveTo evaluate the level of knowledge of medical students about transplantation and brain death. MethodsAn anonymous self-administered questionnaire answered by medical students from the first through the sixth year that was based on information from the Associação Brasileira de Transplante de Órgãos e Tecidos, the Registro Brasileiro de Transplantes and the resolution that defines the criteria for brain death. ResultsOf the 677 medical students asked, 310 (45.8%) agreed to answer the questionnaire. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
1
2
0
4
Order By: Relevance
“…The present study showed that dental students in Brazil receive little education regarding organ donation and transplantation, including information about brain death. These results are in-line with other studies that have used questionnaires to assess the knowledge of students in healthcare on this subject (Bitencourt et al, 2007;Lima et al, 2010;Reis et al, 2013;Dibo et al, 2017;Fontana et al, 2017;Srinivasula et al, 2018;Tackmann, Kurz, and Dettmer, 2020).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The present study showed that dental students in Brazil receive little education regarding organ donation and transplantation, including information about brain death. These results are in-line with other studies that have used questionnaires to assess the knowledge of students in healthcare on this subject (Bitencourt et al, 2007;Lima et al, 2010;Reis et al, 2013;Dibo et al, 2017;Fontana et al, 2017;Srinivasula et al, 2018;Tackmann, Kurz, and Dettmer, 2020).…”
Section: Methodssupporting
confidence: 91%
“…The limited knowledge of the dental program undergraduates in our study reinforces the evidence of an inadequate approach regarding donation and transplantation of the current dental curriculum. Other Brazilian studies evaluating undergraduate medical students have also highlighted the lack of education and training regarding organ donation and transplantation during medical courses (Bitencourt et al, 2007;Reis et al, 2013;Dibo et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…As principais causas de lesão neurológica grave são causadas por traumatismo crânio encefálico, ocasionadas por acidentes de motocicletas e acidente vascular cerebral hemorrágico, fortemente, relacionado com a hipertensão arterial (1)(2)(3)(4) . Quando ocorre a lesão neurológica grave, ocorre edema cerebral e hipertensão intracraniana, levando o paciente a depender de ventilação mecânica, além da necessidade de cuidados intensivos.…”
Section: Introductionunclassified
“…Quando ocorre a lesão neurológica grave, ocorre edema cerebral e hipertensão intracraniana, levando o paciente a depender de ventilação mecânica, além da necessidade de cuidados intensivos. Muitas vezes, o quadro clinico piora e leva a isquemia do cérebro e consequentemente a Morte Encefálica (ME) (1)(2)(3)(4) . A hospitalização do paciente na Unidade de Terapia Intensiva (UTI) pode acontecer a qualquer momento, visto serem patologias agudas e graves, com grande instabilidade hemodinâmica e risco de morte (1)(2)(3)(4) .…”
Section: Introductionunclassified
See 1 more Smart Citation